141k views
13 votes
Use the expression below:

5b + 3c - 20 + 3b - 15c + 4

Part A: Simplify the expression and write it down
Part B: Factor the simplified expression and write it down
Part C:What is the value of the expression when b=2 and c= -3

1 Answer

10 votes

Answer:

Part A: 8b -12c -16

Part B: 4(2b - 3c -4)

Part C: 36

Explanation:

Part A:

5b + 3c - 20 + 3b - 15c + 4

= 8b -12c -16

Part B:

Factorising 8b -12c -16

= 4(2b - 3c -4)

Part C:

= 4[2(2)-3(-3)-4)]

= 4[4+9-4]

= 4[9]

= 36

User William Linton
by
6.3k points